Trends in land use and evalutin of land use policy of Bangladesh: a case study of Muradpur Mouza of Chittagong metropolitan city - Hossain, Md. Tofazzel (BRAC University, 2010)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Governance and Development, 2008.